Psychological And Sociopolitical Perspectives In Norman Mailer’s The Naked And The Dead - Mr. Vijaya Palaniraja; Dr.G. Arputhavel Raja (Revista Electronica de Veterinaria, 2024)
A prominent figure in post-war American writing, Norman Mailer addresses psychological and societal concerns in The Naked and the Dead (1948) that left readers and critics perplexed. He brought them together in a complementary manner that clarified the evolution of their cause and effect. This study explains the different reasons why people gain power, how it hurts both those who abuse it and those who are abused, and how it affects people’s minds and society when it comes to megalomania. It also seeks to expose the inner thoughts of the modern person, who is afflicted by spiritual decay as a form of resistance against the political life that permeates practically every sphere of American society. Mailer’s strong and prominent characters, such as General Cummings and Lieutenant Croft, who embody the victimizers’ megalomaniacal mindsets, serve to illustrate these issues. Lieutenant Hearn and Troop Red Valsen, two additional helpless persons who would suffer at the hands of the victimizers, have always been the focus. In this book, Mailer urges the reader to either give in to immoral influences or make an effort to achieve some degree of spiritual autonomy and self-respect.